2020
DOI: 10.1002/rmv.2112
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of confirmed COVID‐19 with SARS and MERS cases ‐ Clinical characteristics, laboratory findings, radiographic signs and outcomes: A systematic review and meta‐analysis

Abstract: Introduction: Within this large-scale study, we compared clinical symptoms, laboratory findings, radiographic signs, and outcomes of COVID-19, SARS, and MERS to find unique features. Method:We searched all relevant literature published up to February 28, 2020.Depending on the heterogeneity test, we used either random or fixed-effect models to analyze the appropriateness of the pooled results. Study has been registered in the PROSPERO database (ID 176106).Result: Overall 114 articles included in this study; 52 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 129 publications
2
46
0
1
Order By: Relevance
“…The incidence of PTSD after COVID-19 (20%) is lower than that after MERS or SARS [14]. Although this could be explained by differences in the duration between the outbreak and the investigation of the presence of PTSD, it is also possible that the lower mortality rate (2-5%) for individuals with PTSD due to COVID-19 compared with the higher rates (10-20%) in MERS or SARS, could have affected the lower incidence of PTSD in COVID-19 [15].…”
Section: Discussionmentioning
confidence: 94%
“…The incidence of PTSD after COVID-19 (20%) is lower than that after MERS or SARS [14]. Although this could be explained by differences in the duration between the outbreak and the investigation of the presence of PTSD, it is also possible that the lower mortality rate (2-5%) for individuals with PTSD due to COVID-19 compared with the higher rates (10-20%) in MERS or SARS, could have affected the lower incidence of PTSD in COVID-19 [15].…”
Section: Discussionmentioning
confidence: 94%
“…Compared to severe patients, moderate patients were less frequent to show the following features: traction bronchiectasis (OR = 0.40, 95% CI 0.24-0.67, P = 0.002), consolidation (OR = 0.31, 95% CI 0.15-0.64, P = 0.001), interlobular septal thickening (OR = 0.27, 95% CI 0.14-0.51, P = 0.000), crazy-paving pattern (OR = 0.22, 95% CI 0.11-0.44, P = 0.000), reticulation (OR = 0.20, 95% CI 0.05-0.80, P = 0.023), pleural effusion (OR = 0.19, 95% CI 0.07-0.49, P = 0.001), lymphadenopathy (OR = 0.17, 95% CI 0.07-0.41, P = 0.008), over 2 lobes involved (OR = 0.07, 95% CI 0.03-0.17, P = 0.000), but moderate patients were more likely to have radiographic abnormalities with 1 lobe involved (OR = 13.84, 95% A systemic review and meta-analysis (included 52,251 COVID-19 confirmed patients from China) showed that 84% (95% CI 0.78-0.85) of COVID-19 patients had abnormal radiological findings on chest X-ray and CT scans. The radiological abnormalities of bilateral involvement were 76.8% (95% CI 0.63-0.87), consolidation were 75.5% (95% CI 0.51-0.91), GGOs were 71% (95% CI 0.4-0.9), unilateral involvement were 16.5% (95% CI 0.85-0.30) [48].…”
Section: Implementation Considerationmentioning
confidence: 94%
“…Although previous studies suggested that the basic reproduction number (R0) of SARS‐CoV‐2 was between 2 and 3, the countries with prompt isolation were successful in reducing the reproduction number 1 . Extensive research has shown that the total mortality rate is 5.6%, lower than SARS (13%) and MERS (35%) 2 . But the death toll has far exceeded.…”
Section: Introductionmentioning
confidence: 98%